Agricultural production in Tajikistan: Evidence from twelve districts in Khatlon Province, 2015 - 2023 - Lambrecht, Isabel B.; Akramov, Kamiljon T.; Aliev, Jovidon; Khakimov, Parviz (International Food Policy Research Institute, 2023)
This report presents findings related to changes in household agricultural production between 2015 and 2023 in the twelve districts of Khatlon Province that constitute USAID’s Zone of Influence (ZOI). The analysis relies on household survey data from 2000 households interviewed in February-March 2023, and similar household survey data from 2000 households interviewed in February-March 2015.